Study on Tinau Flood at Butwal: An Evacuation Perspective - Pokharel, Gunakhar; Bhandari, Phanindra Prasad; Khadka, Shree Ram (The Nepali Mathematical Sciences Report, 2025)
The Tinau flood, caused by Tinau River during monsoon, is one of the most devastating disasters in Butwal, densely populated business hub located in Butwal Sub-Metropolitan City, Lumbini Province, Nepal. The flood threatens lives and properties along the riverbank. An efficient evacuation plan for potential flood victims is crucial to save their lives. Mathematical optimization model, in particular, network flow model could be a tool for designing the plan. Literature flourishes mathematical models including network flow models for evacuation planning. In this paper, we study lexicographically maximum contraflow (Lex-Max Contraflow) problem and implement it to real data set for Tinau flood evacuation to propose optimum evacuation route plan along with optimum distribution of evacuees among shelters based on their suitable prioritization.